A forecasting implementation of Box-Jenkins time series analysis - Çelik, Turgut. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
The ultimate effect of a decision generally depends on the outcome of factors that can not be foreseen at the time decision is made. Among wide variety of forecasting methods, the Box-Jenkins approach is known as the application of the more general and statistical based methods of time series analysis. This thesis covers the implementation of Box-Jenkins approach by using computer. A computer software is developed for building univariate and bivariate models, and for making the forecasts. The underlying principles of the Box-Jenkins approach are presented, and a methodology of using the approach is suggested.
Keywords: Time-series analysis.; Box-Jenkins forecasting.